Data Management System For Penetration Test Results At The Aceh Informatics And Coding Communication Agency - Zulfa, Ira; Septima, Richasanty; Ar-ramdhi, Asyam Amrullah (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
In an era rife with evolving cyber threats, government agencies such as the Aceh Communication, Informatics, and Cryptography Agency (Diskominsa Aceh) play a pivotal role in safeguarding information security. Diskominsa Aceh has implemented a penetration testing system to identify vulnerabilities in provincial government websites, enabling proactive mitigation of potential security gaps. However, the primary challenge lies in managing the penetration test data, which currently relies on Microsoft Excel, posing security and efficiency drawbacks. To address this issue, Diskominsa Aceh considers migrating data to a more integrated and secure information management platform. Engaging interns in designing a data management system can offer an effective solution, providing Diskominsa Aceh with innovative technical solutions while offering young generations practical skills development in information technology. Dalam era yang dipenuhi dengan ancaman siber yang terus berkembang, instansi pemerintah seperti Dinas Komunikasi, Informatika, dan Persandian Aceh (Diskominsa Aceh) memainkan peran kunci dalam melindungi keamanan informasi. Diskominsa Aceh telah menerapkan sistem uji penetrasi untuk mengidentifikasi kerentanan dalam situs web instansi pemerintah provinsi, memungkinkan mereka untuk secara proaktif mengatasi potensi celah keamanan. Namun, tantangan utama dalam penerapan sistem ini adalah pengelolaan data hasil uji penetrasi yang masih menggunakan Microsoft Excel, yang memiliki kelemahan dalam keamanan dan efisiensi. Untuk mengatasi masalah ini, Diskominsa Aceh mempertimbangkan migrasi data ke platform manajemen informasi yang lebih terintegrasi dan aman. Melibatkan mahasiswa magang dalam merancang sistem manajemen data dapat menjadi solusi yang efektif, memberikan Diskominsa Aceh solusi teknis yang inovatif dan memberikan kesempatan bagi generasi muda untuk mengembangkan keterampilan praktis dalam teknologi informasi.